RESPON ARSITEKTUR TERHADAP DEGRADASI LAHAN PERTANIAN KAWASAN KEMBANGAN MELALUI PERTANIAN PERKOTAAN VERTIKAL - Fatin Nurlia Sari Dewi; James Erich D. Rilatupa (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Kembangan has a history as an area where the majority of the people's livelihoods are farmers. Kembangan District is one of the sub-districts located in West Jakarta. The current phenomenon is the development of the Kembangan area causing the issue of the agricultural land crisis. The conversion of agricultural green land into other functions continues to occur along with the development of the city. Degradation of agricultural land will have an impact on the loss of the identity of the Kembangan area as an agricultural area and if it continues to increase it can cause food security problems in an area. The method used in this study is a descriptive method by looking at the current facts regarding the degradation of agricultural land in the Kembangan sub-district. The limitation of the research with a city acupuncture approach is that it takes a radius of 3000 meters from the selected area. The design method takes the symbiotic architectural method by analyzing the continuity of history and the needs of current program activities first. The symbiotic architectural method is used to incorporate agricultural programs into urban activities. The aim of this paper is to find an urban agricultural design that adapts to the characteristics of the city. The formation of mass composition takes the metaphorical exploration method of leaf chloroplast geometry. The conclusion obtained from the results of this study is that one way to develop the agricultural industry to maintain food security in the midst of the land crisis is through vertical urban agriculture that adapts architectural engineering technology. Keywords: metaphor architecture; symbiotic architecture; agricultural land degradation; food security Abstrak Kawasan Kembangan memiliki sejarah sebagai kawasan yang mayoritas mata pencaharian masyarakatnya adalah sebagai petani. Kecamatan Kembangan merupakan salah satu kecamatan yang terletak di Jakarta Barat. Fenomena yang terjadi saat ini adalah perkembangan kawasan Kembangan menyebabkan isu krisis lahan pertanian. Alih fungsi lahan hijau pertanian menjadi fungsi lain terus terjadi seiring perkembangan kota. Degradasi lahan pertanian akan berdampak pada hilangnya identitas kawasan Kembangan sebagai kawasan pertanian dan apabila terus meningkat dapat menyebabkan permasalahan ketahanan pangan suatu kawasan. Metode yang digunakan dalam penelitian ini merupakan metode deskriptif dengan melihat fakta yang terjadi saat ini terkait degrasi lahan pertanian di kecamatan Kembangan. Batasan penelitian dengan pendekatan akupuntur kota mengambil radius 3000 meter kawasan terpilih. Metode desain mengambil metode aritektur simbiosis dengan menganalisis kesinambungan sejarah dan kebutuhan aktivitas program saat ini terlebih dahulu. Metode arsitektur simbiosis digunakan untuk memasukan program pertanian ke dalam aktivitas kota. Tujuan yang ingin dicapai dalam penulisan ini adalah untuk menemukan desain pertanian perkotaan yang menyesuaikan karakteristik kota. Pembentukan gubahan massa mengambil metode metafora eksplorasi geometri bentuk kloroplas daun. Kesimpulan yang didapatkan dari hasil penelitian ini adalah salah satu cara mengembangkan industri pertanian untuk menjaga ketahanan pangan ditengah isu krisis lahan melalui pertanian perkotaan vertikal yang mengadaptasi rekayasa teknologi arsitektur.